Psychological Characteristics Of The Emergence Of Stress, Depression, And Role Confusion In Adolescents (Texas Journal of Multidisciplinary Studies, 2026)
This article analyzes the psychological characteristics of adolescence, the biological, psychological, and social factors of school-related stress, Erik Erikson’s stage of “identity vs. role confusion,” identity statuses according to Marcia’s theory, as well as the main forms of behavioral disorders observed in adolescents based on scientific sources